2013
DOI: 10.1186/1471-2229-13-139
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ethylene biosynthesis and signalling in fruit set and early fruit development in zucchini squash (Cucurbita pepoL.)

Abstract: BackgroundWe have identified a kind of parthenocarpy in zucchini squash which is associated with an incomplete andromonoecy, i.e. a partial conversion of female into bisexual flowers. Given that andromonoecy in this and other cucurbit species is caused by a reduction of ethylene production in the female flower, the associated parthenocarpic development of the fruit suggested the involvement of ethylene in fruit set and early fruit development.ResultsWe have compared the production of ethylene as well as the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 45 publications
5
59
0
4
Order By: Relevance
“…Nevertheless, it is known to decline just after fruit set in several species (Vriezen et al, 2008;Wang et al, 2009;Martínez et al, 2013), most likely along with the availability of its immediate precursor 1-aminocyclopropane-1-carboxylate (A. Botton, unpublished data). According to the data provided by the meteorological station located in the experimental orchards, during the 5 d preceding the thinning treatment (10-14 DAPF), mean and maximum temperatures in 2009 were 3.3°C (11.2°C versus 14.5°C) and 6.2°C (15°C versus 21.2°C) lower than in 2008, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is known to decline just after fruit set in several species (Vriezen et al, 2008;Wang et al, 2009;Martínez et al, 2013), most likely along with the availability of its immediate precursor 1-aminocyclopropane-1-carboxylate (A. Botton, unpublished data). According to the data provided by the meteorological station located in the experimental orchards, during the 5 d preceding the thinning treatment (10-14 DAPF), mean and maximum temperatures in 2009 were 3.3°C (11.2°C versus 14.5°C) and 6.2°C (15°C versus 21.2°C) lower than in 2008, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data from tomato and other plant species has suggested that ethylene and ABA might play a role in fruit set, because their production decreases dramatically right after pollination (Vriezen et al, 2008;Nitsch et al, 2009;Pascual et al, 2009;Wang et al, 2009;CarbonellBejerano et al, 2011;Martínez et al, 2013). Our RNA-seq data suggested that the problematic fruit set in the SlZFP2 RNAi lines seems to result from the disturbed action of multiple hormones, because the expression of many genes involved in the biosynthesis and/or perception of auxin, cytokinin, GA, ABA, and ethylene was affected.…”
Section: Slzfp2 Regulates Fruit and Seed Development In Two Tomato Gementioning
confidence: 99%
“…Nonetheless, it is of industrial and ecological interest that 56% of nonpollinated flowers were still able to reach marketable size and shape without any pollination at all. This is owing to the natural parthenocarpic tendency of courgettes, previously observed in Tosca (Mart ınez et al 2013) and other varieties (Robinson and Reiners 1999). However, Mart ınez et al (2013) concluded that Tosca was not truly parthenocarpic, as fruits consistently showed a burst in ethylene around 3 d after anthesis, which is thought to cause early fruit abortion in nonpollinated flowers.…”
Section: Discussionmentioning
confidence: 67%
“…For example, 22 out of the 33 summer squash varieties have been shown to set fruit without pollination (Robinson and Reiners 1999). Likewise, fruit set without pollination has also been observed in cucumber (Kushnereva 2008), watermelon (Sedgley et al 1977), and additional varieties of summer squash (Kurtar 2003;Mart ınez et al 2013Mart ınez et al , 2014. This type of fruit set, without pollination and therefore fertilization, is parthenocarpy.…”
mentioning
confidence: 85%